Post herpes zoster SUNCT like syndrome: Insights from two case reports. (February 2018) - Mathew, Thomas; Srinivas, Meghana; Badachi, Sagar; Nadig, Raghunandan
Background: SUNCT like syndrome secondary to post herpes zoster infection has not been reported in literature. Case: We are reporting two cases of SUNCT like syndrome secondary to post herpes zoster infection of the V1 distribution of the trigeminal nerve. Treatment with pregabalin and lamotrigine achieved complete symptomatic relief in both patients. Conclusion: SUNCT like syndrome can occur after herpetic infection of the trigeminal nerve. Unlike primary SUNCT syndrome, post-herpetic SUNCT like syndrome seems to respond well to pharmacological treatment and has a good prognosis.